Modelo numérico de viga mista de aço e concreto composta por perfil formado à frio e conectores do tipo parafuso com rebite - Karen Aparecida Freitas Peroni Maia (2018)
The strength and the stiffness of connection between the steel profile and the concrete slab composite beams are in direct function of the amount used and the shear connectors properties used. If these connectors are flexible, the contribution of friction is accentuated both the consideration of the serviceability limit states as to the ultimate limit states. The requirements of the Brazilian, American and European Standards do not include the influence of friction in composite beams although they consider to composite slabs with embedded steel shape. This work is part of an extensive theoretical-experimental research supervision by professors of the UFMG that aims to investigate the behavior of composite beams using tubular rivet type shear connectors with internal thread and bolts with hex head. In this case, the study focuses on the evaluation of the behavior of such composite beams face the presence of friction at the steel profile - concrete slab interface. Using a numerical methodology in finite elements, using ABAQUS® software, validation of the experimental results performed in the Laboratory of Experimental Analysis of Structures of UFMG, for connectors push tests and for composite beams with and without a presence of friction. Once validated the numerical methodology will be developed a critical analysis to evaluate the friction contribution in the behavior of composite beams with flexible and ductile shear connectors.